Mapping RDEVSNL-based Definitions of Constrained Network Models to Routed DEVS Simulation Models - Espertino, Clarisa; Julia Blas, Maria; Gonnet, Silvio (Journal of the Brazilian Computer Society, 2024)
The Routed DEVS (RDEVS) formalism has been introduced recently to provide a reasonable formalization for the simulation of routing processes over Discrete Event System Specification (DEVS) models. Due to its novelty, new software tools are required to improve the Modeling and Simulation (MS) tasks related to the RDEVS formalism. This paper presents the mapping between constrained network models obtained from textual specifications of routing processes and RDEVS simulation models implemented in Java. RDEVSNL context-free grammar (previously defined) is used to support the textual specification of a routing process as a constrained network model. Such grammar is based on a metamodel that defines the syntactical elements. This metamodel is used in this paper as a middleware that allows mapping constrained network model concepts with RDEVS simulation models. From such a constrained network model template, RDEVS Java implementations are obtained. The proposal is part of a work-in-progress intended to develop MS software tools for the RDEVS formalism using well-known abstractions to get the computational models through conceptual mapping. Using these tools, modelers can specify simulation models without needing to codify any routing implementation. The main benefits are i) reduction of implementation times and ii) satisfactory simulation model correctness regarding the RDEVS formalism.